Evaluation of different positive end-expiratory pressures using supreme™ Airway Laryngeal Mask during minor surgical procedures in children - Fiedler-Kalenka, Mascha; Schätzle, Elisabeth Barbara; Contzen, Marius; Gernoth, Christian; Weiß, Christel; Walter, Thomas; Viergutz, Tim; Kalenka, Armin (Medicina, 2020)
Background and objectives: The laryngeal mask is the method of choice for airway management in children during minor surgical procedures. There is a paucity of data regarding optimal management of mechanical ventilation in these patients. The Supreme™ airway laryngeal mask offers the option to insert a gastric tube to empty the stomach contents of air and/or gastric juice. The aim of this investigation was to evaluate the impact of positive end-expiratory positive pressure (PEEP) levels on ventilation parameters and gastric air insufflation during general anesthesia in children using pressure-controlled ventilation with laryngeal mask. Materials and Methods: An observational trial was carried out in 67 children aged between 1 and 11 years. PEEP levels of 0, 3 and 5 mbar were tested for 5 min in each patient during surgery and compared with ventilation parameters (dynamic compliance (mL/cmH2O), etCO2 (mmHg), peak pressure (mbar), tidal volume (mL), respiratory rate (per minute), FiO2 and gastric air (mL)) were measured at each PEEP. Air was aspirated from the stomach at the start of the sequence of measurements and at the end. Results: Significant differences were observed for the ventilation parameters: dynamic compliance (PEEP 5 vs. PEEP 3: p < 0.0001, PEEP 5 vs. PEEP 0: p < 0.0001, PEEP 3 vs. PEEP 0: p < 0.0001), peak pressure (PEEP 5 vs. PEEP 3: p < 0.0001, PEEP 5 vs. PEEP 0: p < 0.0001, PEEP 3 vs. PEEP 0: p < 0.0001) and tidal volume (PEEP 5 vs. PEEP 3: p = 0.0048, PEEP 5 vs. PEEP 0: p < 0.0001, PEEP 3 vs. PEEP 0: p < 0.0001). All parameters increased significantly with higher PEEP, with the exception of etCO2 (significant decrease) and respiratory rate (no significant difference). We also showed different values for air quantity in the comparisons between the different PEEP levels (PEEP 5: 2.8 ± 3.9 mL, PEEP 3: 1.8 ± 3.0 mL; PEEP 0: 1.6 ± 2.3 mL) with significant differences between PEEP 5 and PEEP 3 (p = 0.0269) and PEEP 5 and PEEP 0 (p = 0.0209). Conclusions: Our data suggest that ventilation with a PEEP of 5 mbar might be more lung protective in children using the Supreme™ airway laryngeal mask, although gastric air insufflation increased with higher PEEP. We recommend the use of a laryngeal mask with the option of inserting a gastric tube to evacuate potential gastric air.
Gesehen am 21.07.2025